Галловая нематода и борьба с ней в защищенном грунте Донецкого ботанического сада НАН Украины - Бондаренко-Борисова, И.В.; Деревянская, А.Г.; Болтовская, Е.В.; Сигарёва, Д.Д. (Промышленная ботаника, 2006)
Seventeen plant species damaged by root-knot nematode were registered at the Donetsk Botanical Gardens conservatories during 2004 – 2005. Representatives of Ficus sp., Begonia sp., Passiflora sp., Azorina sp. genera suffered more heavily. Original data were obtained for Meloidogyne incognita control under conservatory conditions of the Donetsk Botanical Gardens. These data concern possibility of Artemisia absinthium L. allelopathic abilities using, anthelminthic and catch crops (Cucumis sativus L., Vicia faba L., Pisum sativum L.) using. Conducted researches showed high effectiveness of A. absinthium mulch using in meloidogynosis combating when Solanum pseudocapsicum L. being infected artifically. C. sativus showed the best catching abilities among four tried cultures. It reduced Meloidogyne incognita invasion larvae density by 75,3%. Taking into account the current Ukrainian Law that prohibits any soil disinfectants using at the conservatories, working out and implementation of ecological safe methods of root-knot nematode control are extremely actual.